Physical activity levels in asthma: relationship with disease severity, body mass index and novel accelerometer-derived metrics. (3rd April 2023) - Ricketts, Helen Clare; Buchan, Duncan S.; Steffensen, Femke; Chaudhuri, Rekha; Baker, Julien S.; Cowan, Douglas C.
Abstract: Objectives: Patients with asthma may feel limited in physical activity (PA). Reduced PA has been demonstrated in asthmatics versus healthy controls, and increasing PA associated with improved asthma outcomes. Obesity is commonly found with difficult-to-control asthma and worsens outcomes. We compared PA levels in participants with difficult-to-control asthma and elevated body mass index (BMI) (DOW group) and two mild-moderate asthma groups: one with BMI <25 kg/m 2 (MHW) and one with BMI ≥25 (MOW). Methods: This cross-sectional study used 7-day recordings from wrist-worn accelerometers to compare PA between groups. Inactive time, light (LPA), moderate-vigorous PA (MVPA) were measured, along with two novel metrics: intensity gradient (IG) reflecting PA intensity, and average acceleration (AA) reflecting PA volume. PA parameters were compared using ANOVA or Kruskall-Wallis testing. Correlation and linear regression analyses explored associations between PA parameters and asthma outcomes. As AA was the PA parameter correlated most closely with asthma-related outcomes, an exploratory analysis compared outcomes in highest and lowest AA quartiles. Results: 75 participants were recruited; 57 accelerometer readings were valid and included in analysis. Inactive time was significantly higher ( p  < 0.001), and LPA ( p  < 0.007), MVPA ( p  < 0.001), IG ( p  < 0.001) and AA ( p  < 0.001) all significantly lower in DOW versus MHW and MOW groups, even after adjusting for age and BMI. Quartiles based on AA had significantly different asthma profiles. Conclusions: Overweight/obese participants with difficult-to-control asthma performed less PA, and activity of reduced intensity and volume. Increased AA is associated with improvement in several asthma-related outcomes. Increased PA should be recommended to relevant patients.